Progression of skeletal muscle damage during treatment of severe falciparum malaria - Timothy M.E. Davis (2018)
To assess the relationship between severity of malaria and progression of skeletal muscle damage during initial treatment, we studied 28 Thai adults with slide-positive falciparum malaria. Six had uncomplicated malaria (Group 1), 12 had severe non-cerebral malaria (Group 2) and ten had cerebral malaria (Group 3). There were no significant differences between baseline serum creatine kinase (CK) levels in the three groups (P = 0.071). There was no change in serum CK during the first 48 h of treatment in Group 1 cases. In Group 2 patients, the median peak serum CK was nine times that at baseline while in Group 3, serum CK peaked at a median concentration 20 times that at presentation. In Groups 2 and 3, the peak serum CK occurred at least 24 h after presentation in more than half the patients, and was independent of intramuscular injections and convulsions during initial therapy. These longitudinal data suggest that: (i) severe falciparum malaria is associated with skeletal muscle damage that increases during initial therapy especially in patients with coma; (ii) the effect of other major treatment or infection- specific factors that are associated with muscle damage does not diminish this relationship; and (iii) cerebral malaria in combination with a high baseline and rising serum CK should pre-empt monitoring and management strategies aimed at preserving renal function including renal dialysis. (C) 2000 Elsevier Science B.V.